Estudo das relações - Gomes, Lúcia Pereira dos Santos (2013)
The purpose of this monograph is to make a detailed study about studying of relations. So, we will provide some definitions. Developing this Themes like binary relations, equivalence relations and order relations. At the same we will show ways to represent relations highlighting the representation in the form of graphs. And we will finish the job with Topological Ordering in completing some tasks of a project.